Why Generation Z Intends to Save in Islamic Banks: A Case in Indonesia - Fitria, Lia; Priantina, Anita (Ekonomi Islam Indonesia, 2025)
The growth of the Islamic banking industry continues to show a positive trend, both at the global and national levels. One indicator is the increase in banking products, especially savings products. This study aims to analyze the influence of financial literacy and religiosity on intention to save at Islamic banks among Generation Z, with a focus on high school students in Bogor City. This study uses a quantitative approach by involving 100 respondents from SMA Negeri 1 Citeureup students. Data were collected through questionnaires, and analyzed using the Structural Equation Modeling (SEM) method. The results of the analysis show that both financial literacy and religiosity have a positive and significant influence on intention to save at Islamic banks. The R-Square value on the intention to save construct is 0.801, which indicates that 80.1% of the variability in intention saving can be explained by these two variables. The findings emphasize the importance of increasing financial and religious education to encourage wider awareness and participation in sharia-based financial practices.